Randomised, prospective, medico-economic nationwide French study of islet transplantation in patients with severely unstable type 1 diabetes: the STABILOT study protocol. Issue 2 (20th February 2017) - Lablanche, Sandrine; David-Tchouda, Sandra; Margier, Jennifer; Schir, Edith; Wojtusciszyn, Anne; Borot, Sophie; Kessler, Laurence; Morelon, Emmanuel; Thivolet, Charles; Pattou, François; Vantyghem, Marie Christine; Berney, Thierry; et al.
Abstract : Introduction: Islet transplantation may be an appropriate treatment option for patients with severely unstable type 1 diabetes experiencing major glucose variability with severe hypoglycaemia despite intensive insulin therapy. Few data are available on the costs associated with islet transplantation in relation to its benefits. The STABILOT study proposes to assess the economic impact of islet transplantation in comparison with the current best medical treatment defined as sensor-augmented pump (SAP) therapy. Methods: The trial will adopt an open-label, randomised, multicentred design. The study will include 30 patients with severely unstable type 1 diabetes. Eligible participants will be 18–65 years old, with type 1 diabetes duration >5 years, a negative basal or stimulated C-peptide, and severe instability defined by persistent, recurrent and disabling severe hypoglycaemia, despite optimised medical treatment. Participants will be randomised into two groups: one group with immediate registration for islet transplantation, and one group with delayed registration for 1 year while patients receive SAP therapy. The primary endpoint will be the incremental cost-utility ratio at 1 year between islet transplantation and SAP therapy. Perspectives of both the French Health Insurance System and the hospitals will be retained. Ethics and dissemination: Ethical approval has been obtained at all sites. The trial has been approved by ClinicalTrials.gov (Trial registration ID NCT02854696 ). All participants will sign a free and informed consent form before randomisation. Results of the study will be communicated during national and international meetings in the field of diabetes and transplantation. A publication will be sought in journals usually read by physicians involved in diabetes care, transplantation and internal medicine. Trial registration number: NCT02854696 ; Pre-results.